Biomarkers for predicting central neuropathic pain occurrence and severity after spinal cord injury: results of a long-term longitudinal study. Issue 3 (March 2020) - Gruener, Hila; Zeilig, Gabi; Gaidukov, Evgeni; Rachamim-Katz, Orna; Ringler, Erez; Blumen, Nava; Engel-Haber, Einat; Defrin, Ruth
Abstract : Abstract: Central neuropathic pain (CNP) after spinal cord injury (SCI) is debilitating and immensely impacts the individual. Central neuropathic pain is relatively resistant to treatment administered after it develops, perhaps owing to irreversible pathological processes. Although preemptive treatment may overcome this shortcoming, its administration necessitates screening patients with clinically relevant biomarkers that could predict CNP early post-SCI. The aim was to search for such biomarkers by measuring pronociceptive and for the first time, antinociceptive indices early post-SCI. Participants were 47 patients with acute SCI and 20 healthy controls. Pain adaptation, conditioned pain modulation (CPM), pain temporal summation, wind-up pain, and allodynia were measured above, at, and below the injury level, at 1.5 months after SCI. Healthy control were tested at corresponding regions. Spinal cord injury patients were monitored for CNP emergence and characteristics at 3 to 4, 6 to 7, and 24 months post-SCI. Central neuropathic pain prevalence was 57.4%. Central neuropathic pain severity, quality, and aggravating factors but not location somewhat changed over 24 months. Spinal cord injury patients who eventually developed CNP exhibited early, reduced at-level pain adaptation and CPM magnitudes than those who did not. The best predictor for CNP emergence at 3 to 4 and 7 to 8 months was at-level pain adaptation with odds ratios of 3.17 and 2.83, respectively (∼77% probability) and a cutoff value with 90% sensitivity. Allodynia and at-level CPM predicted CNP severity at 3 to 4 and 24 months, respectively. Reduced pain inhibition capacity precedes, and may lead to CNP. At-level pain adaptation is an early CNP biomarker with which individuals at risk can be identified to initiate preemptive treatment. Abstract : Pain adaptation test predicts central neuropathic pain after spinal cord injury with high probability and sensitivity and can be used to identify individuals at risk.